Development and regulation of cellular and gene therapy products: FDA perspective - Lapteva, Larissa (Henry Stewart Talks, 2021)
Cellular and gene therapy products, U.S. laws and regulations, FDA review, Product development considerations, Regulatory considerations, Product manufacturing stages and quality testing, Safety, efficacy and ethical considerations for clinical program design, FDA Guidance documents